Latin America and the Caribbean in the World Economy 2013 - Economic Commission for Latin America; the Caribbean (United Nations, 2014)
The 2013 edition of this publication reviews the main features of a persistently weak global economy and world trade and then turns to global and regional trade trends and prospects. The publication considers the main changes in the organization of production and global trade associated with international production networks, which are at the heart of current mega-regional negotiations. It looks at how the region's countries are positioned in international production networks and value chains. It analyzes the main factors underpinning participation in production networks and value chains, as well as the implications they have for integration.